Individualize Outcome Evaluation Program Rehabilitasi Sosial Anak Berkonflik Hukum (ABH) di BRSAMPK Rumbai. - Satifa, Rieza; Adi, Isbandi Rukminto (Jurnal Ilmu Kesejahteraan Sosial, 2020)
This study aims to individually evaluate the impact (Outcomes) of a social rehabilitation program for Children in Legal Conflict (ABH) in BRSAMPK Rumbai. One of the programs available is the Rumah Antara that is intended for ABH who have already been or are undergoing legal proceedings. By using a qualitative approach, this research evaluated ABH who have carried out social rehabilitation and have resumed life in their communities, so that they can provide a pattern and input to the Balai and the justice system in handling child with criminal cases. Past conditions cause the family to be more possessive to children, and it makes the child shows an attitude contrary to parents. By using the interview, observation, and documentation study methods of the results of this study indicate the achievement of program success indicators at the outcome stage, namely: children no longer commit unlawful acts, children return to their families and communities, positive attitude and behavior changes, and children receive care and protection from his family.